PENGARUH ORIENTASI PASAR, ORIENTASI PEMBELAJARAN DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING IKM (SENTRA IKM TENUN IKAT TROSO KABUPATEN JEPARA) - Aristin Nikmah; Ari Pradhanawati; Wahyu Hidayat (Universitas Diponegoro, 2015)
Competitive advantage is influenced by several factors, including learning orientation, market orientation and product innovation. However, the efforts made to improve the learning orientation, market orientation's understanding, and product innovation by IKM owners still less attention. The purpose of this research is to recognize and explain the influence of learning orientation, market orientation, and product innovation towards competitive advantage of IKM centers Ikat Troso, Jepara District. This research uses explanatory research approach to 76 respondents with simple random technique. Data collection techniques in this study using the technique of interviews, questionnaires, observation and study of literature. The analysis technique used is qualitative and quantitative. Quantitative analysis using frequency tables, cross-tables analysis, validity test, reliability test, simple linear regression, multiple linear regression and test of significance (t-test and F-test) and also use the help application programs SPSS 20.0 for Windows. Results of this research known partial effect between learning orientation, market orientation and product innovation has a positif and significant influence to the competitive advantage by 30%, 28%, 28,9% and the simultaneous influence by 31.5%. Based on these conclusions, then owner IKM need to pay attention to the things about a commitment with learning, orientation towards the customers, the creation of new products and the uniqueness of the product, because it’s has the lowest average.